2.4/5.8 GHz WLAN Filtering in Secure Electromagnetic Applications: A Single Layer Frequency Selective Surface. Issue 4 (2nd October 2017) - Majidzadeh, Maryam
Abstract: This paper aims to propose a novel frequency selective surface (FSS) sketch for 2.45 and 5 GHz WLAN protection applications. The proposed FSS unit cell is printed on 10 × 10 mm 2 FR4 substrate with thickness of 1.6 mm. Simple conductive elements are printed on top and bottom sides of the single substrate layer. Wise inclusion of elements and precise tuning of their dimensions yields in rejection of two frequency bands in 2.45 and 5 GHz WLAN frequency bands. The presented structure exhibit stable response against different angles of TE and TM polarized waves. Suitable performance of the designed FSS makes it a suitable choice for use in secure electromagnetic buildings, and communication filtering applications. Abstract :